Screening and Identification of Potential Fungi from polluted Soil for the Bioremediation of Copper and Lead - Fernando, A. S . Manasha Savithri (2016)
Heavy metal pollution is one of the most prominent environmental problems faced by countries all over the world, leading to extensive research in how to eliminate this problem. Out of several available methods for environmental detoxification, bioremediation is gaining popularity due its multi-advantageous process. The use of fungi is one of the best ways to remediate heavy metals in soil. This study focuses on the screening and isolation of fungi from polluted soil for the bioremediation of copper and lead, using rose Bengal agar and potato dextrose agar. Fourteen different fungal species were identified using microscopic and macroscopic analysis and were subsequently subjected to heavy metal toxicity testing using lead and copper. Among all isolated species, Trichoderma sp., F. oxysporum, P. citri and Fusarium sp. 1 were found to be good candidates for the bioremediation of both lead and copper, while Mucor sp. showed promising results with lead and Fusarium sp. 2 showed good results with copper.